(untitled) (Revista científica Olimpia, 2021)
The bronchial asthma is the commonest chronic illness in pediatric ages and the principal cause of hospital confinement in Cuba. The physical exercise applied to the asthmatic one is understood inside the means that compose the therapeutic strategy designed for the same ones, combining in a harmonious and personalized form with the rest of the therapeutic methods, however, the insufficient use of the auxiliary means, restrict the correct rehabilitation of the asthma in children, that is why it is proposed to elaborate a set of auxiliary means to favor the rehabilitation of the asthma in children of 8 to 12 years of Báguanos’s municipality. For the logic of investigation methods of the theoretic level, empiric and within this the techniques of consent were utilized. The proposed means fulfills a series of basic characteristics in agreement with the pupils’ possibilities, with the limits of the environment and with the marked objectives in the programming, as a result six means were made. Evaluated of very appropriate for specialists in the nominal group, since it offers possibilities of application, possess practical sense, adaptability, certainty and profitability-duration. The application of the statistical methods, verified that difference exists among the measurements in the studied cases that allows affirming the positive effect of the employed means to favor the rehabilitation of the bronchial asthma in children.